Sexual Dimorphism in the Age-Induced Insulin Resistance, Liver Steatosis, and Adipose Tissue Function in Rats - Garcia-Carrizo, Francisco; Priego, Teresa; Szostaczuk, Nara; Palou, Andreu; Picó, Catalina (Frontiers in Physiology, 2017)
Age-linked metabolic disturbances, such as liver steatosis and insulin resistance, show greater prevalence in men than in women. Thus, our aim was to analyze these sex-related differences in male and female Wistar rats (aged 26 days and 3, 7 and 14 months), and to assess their potential relationship with alterations in the capacity of adipose tissue expansion and the dysregulation of the main adipokines produced by the adipose tissue, leptin and adiponectin. Adiposity-related parameters, blood parameters, the expression of genes related to expandability and inflammation (WAT), lipid metabolism (liver), and leptin and insulin signaling (both tissues) were measured. In females, adiposity index and WAT DNA content gradually increased with age, whereas males peaked at 7 months. A similar sex-dependent pattern was observed for leptin expression in WAT, while Mest expression levels decreased with age in males but not in females. Females also showed increased expression of the proliferation marker PCNA in the inguinal WAT compared to males. In males, leptin/adiponectin ratio greatly increased from 7 to 14 months in a more acute manner than in females, along with an increase in HOMA-IR index and hepatic triacylglyceride content, while no changes were observed in females. In liver, 14-month-old males displayed decreased mRNA levels of Insr, Ampkα2, and Cpt1a compared with levels at 7 months. Males also showed decreased mRNA levels of Obrb (both tissues), and increased expression levels of Cd68 and Emr1 (WAT) with age. In conclusion, females are more protected from age-related metabolic disturbances, such as insulin resistance, hepatic lipid deposition, and WAT inflammation compared to males. This may be related to their greater capacity for WAT expansion - reflected by a greater Mest/leptin mRNA ratio - and to their ability to maintain adiponectin levels and preserve leptin sensitivity with aging.